Challenges and Strategies for Implementing 21st-century Learning Hindu Religious Education and Ethics at UPT SD Negeri 5 Amparita - Jevisa, Tommy; Suwendra, I Wayan (Jayapangus Press, 2024)
Information and communication technology use in learning is a demand for the development and progress of today's increasingly modern era. Education in Indonesia must continue to improve and adjust to the rapid development of globalization. Teachers, as agents of renewal and spearheads in realizing national education goals, must continue to develop all their abilities and competencies in designing and implementing exciting learning for students. Teachers in Indonesia today must continue to try their best to create creative, innovative, and competitive students. For this reason, a strategy for implementing 21st-century learning is needed, and it is expected to be able to explore and improve the 4C skills of students. This study aims to provide an overview of the challenges and appropriate strategies used in applying 21st-century learning to Hindu religious education and ethics subjects at UPT SD Negeri 5 Amparita. This qualitative research uses data collection techniques that involve conducting in-depth observations and interviews. The results showed that (1) there are challenges in the application of 21st-century learning both internally and externally, and (2) to overcome these challenges, the right strategy is needed in efforts to implement 21st-century learning at UPT SD Negeri 5 Amparita. 21st-century learning is very important to be applied at UPT SD Negeri 5 Amparita because, in addition to being a demand from developments in the era of globalization, it is also because it is in line with the vision and mission of the school in creating students who are communicative, creative and innovative, think critically, and can work together.